2006
DOI: 10.1111/j.1532-5415.2006.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Hospital at Home Care

Abstract: Hospital at Home care was associated with greater satisfaction than acute hospital inpatient care for patients and their family members. These findings support further dissemination of the Hospital at Home care model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 19 publications
4
93
0
8
Order By: Relevance
“…Hastalık sürecinde yaşanan zorluklar hasta birey kadar aileyi de etkilemektedir [2,4,6]. Ailedeki bakım vericiler hastanın yardıma ihtiyacı olan konuların belirlenmesi, semptomların tedavisinin sürdürülmesi, beklenmedik tıbbi sorunların ortaya çıkmasının ve tekrarlı hastane yatışlarının önlenmesi gibi birçok konuda sorumluluk almaktadır [2,[7][8][9][10]. Bakım vericilerinin KOAH'lı hastaların hastalık semptomlarının izleminde, hastaların semptom yönetimini başarmalarında ve sağlık ekibi ile iletişimi sürdürmede olumlu etkilerinin olduğu belirlenmiştir [10].…”
unclassified
“…Hastalık sürecinde yaşanan zorluklar hasta birey kadar aileyi de etkilemektedir [2,4,6]. Ailedeki bakım vericiler hastanın yardıma ihtiyacı olan konuların belirlenmesi, semptomların tedavisinin sürdürülmesi, beklenmedik tıbbi sorunların ortaya çıkmasının ve tekrarlı hastane yatışlarının önlenmesi gibi birçok konuda sorumluluk almaktadır [2,[7][8][9][10]. Bakım vericilerinin KOAH'lı hastaların hastalık semptomlarının izleminde, hastaların semptom yönetimini başarmalarında ve sağlık ekibi ile iletişimi sürdürmede olumlu etkilerinin olduğu belirlenmiştir [10].…”
unclassified
“…destacan varios trabajos de la universidad John Hopkins (8)(9)(10). En España, cabe señalar la revisión realizada desde la óptica de la geriatría en 2015 (11).…”
Section: Algunos Resultadosunclassified
“…Leff et al found that family members are more satisfied with treatment and care at home than with the hospital. [10] Similarly, Wilson et al found that caregivers in the primary health care feel that hospital at home does not produce a higher burden of care. [5] The relatives in our study were at least just as satisfied as the patients.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In the quantitative studies, the questionnaires are either poorly described [4,9] or long and time-consuming (a 40-question survey). [10] Richards et al used an 11-item patient satisfaction questionnaire to compare hospital at home with routine hospital care. [11] However, the validity of that questionnaire was unclear.…”
Section: Introductionmentioning
confidence: 99%